Desk references for hematology - Shinton ,N. K. (CRC Press, 2008)
A cross between a dictionary and an encyclopedia, this title presents an examination of hematology. It includes revised articles emphasizing genetics, physiology, pathological mechanisms; coverage of treatments for leukemia, lymphoma, coagulation, and thrombotic disorders; and a hundred articles, illustrations, and explanatory diagrams.